Perception and effects among the Arts and Sciences community of the University of El Salvador about the “open-door glossary” project (Nahuat, Castilian Spanish, English and French) during the second semester of 2016 - Alvarado Guevara, José Miguel; Cerón Cisneros, Carmen Nohemí; Paz Pérez, Bryan Alberto (2024)
Nahuat has been spoken in several places of El Salvador like Nonualcos, Cuzcatlecos, Mazhuas and Izalcos, it happens to be Salvadoran mother tongue and represents the roots of a culture that nowadays has been left aside because of several reasons. In the Arts and Science School of the University of El Salvador takes place a new and innovative program to start rescuing Nahuat. This new idea was launched by Linguistics students to deploy a glossary all around the School so it has called other students’ attention. The goal of this project is to wake up people’s willingness of being part of Nahuat rescue. After the glossary project was launched, the research team is looking for the perception and the effect that it has had in the student’s community in three different areas, identity, education and culture, how it has evolved and to show the next step of it to continue with its mission of Nahuat preservation. As all this considered, the research team is looking for the output that a brand new idea and project has had in the aims of Nahuat rescue, considering that more than a language, it represents cultural roots and history for a country that on its willingness to reach globalized development has left behind its essence.